Dinamika Evolusi Penelitian Green Finance: Analisis Bibliometrik pada Artikel Ilmiah Bereputasi Internasional - Olii, Nurhayati; Mustafa, Muh. Sabir; Solikahan, Eka Zahra (Al-Buhuts, 2025)
This study aims to map green finance research trends through a bibliometric analysis of internationally reputable scientific articles indexed in Scopus over the past decade. The methodology employed involves bibliometric analysis based on secondary data obtained from the Scopus database, encompassing the processes of collecting publication data, normalizing keywords, mapping collaborative networks, and identifying topic trends using bibliometric analysis software. The results indicate a significant increase in research related to green finance, with China being the most prominent country in academic publications. Major educational institutions and reputable journals such as Sustainability (Switzerland) play an essential role in supporting the development of literature in this field. Key topic trends in green finance research include sustainability, carbon emission reduction, financial innovation, green investment, and green finance policy. Challenges in the implementation of green finance include suboptimal regulations and limited access to green investment. Therefore, global collaboration, strengthening regulations, and the adoption of digital financial technology are needed to increase the effectiveness of green finance in supporting the green economy.